High frequency ultrasonic assisted mass-transfer for water batch reactor - Tay, W.H. (Asian Research Publishing Network, 2016)
Ultrasonic assisted mass transfer is one of the potential alternatives that possess the advantages of high mass transfer enhancement with absence of moving part. A higher frequency ultrasonic irradiation generates a higher streaming turbulent force. However, most of the current studies are performed under low frequency ultrasonic irradiation. In this paper, a high frequency ultrasonic assisted mass transfer was studied in a water batch reactor. The mass transfer coefficient was determined by the dynamic pressure step method. The power of the ultrasonic irradiation was measured using calorimetric method. The result showed that, approximate 28 power from the electrical dissipation power has been converted to the ultrasonic irradiation power. Besides, based on the experimental result, the mass transfer coefficient has been significantly enhanced by the ultrasonic irradiation up to 20 times faster for CO2 desorption as compared to the case without ultrasonic irradiation. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.